2011
DOI: 10.1107/s1744309111029009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor-bound complexes of dihydrofolate reductase-thymidylate synthase fromBabesia bovis

Abstract: Babesiosis is a tick‐borne disease caused by eukaryotic Babesia parasites which are morphologically similar to Plasmodium falciparum, the causative agent of malaria in humans. Like Plasmodium, different species of Babesia are tuned to infect different mammalian hosts, including rats, dogs, horses and cattle. Most species of Plasmodium and Babesia possess an essential bifunctional enzyme for nucleotide synthesis and folate metabolism: dihydrofolate reductase‐thymidylate synthase. Although thymidylate synthase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…To elucidate a structural basis for the difference in resistance profiles to DHFR inhibitors of the G137D and A71V mutants in DHFR‐TS1 and DHFR‐TS2, respectively, we modelled the structure of A. thaliana DHFR‐TS1 and DHFR‐TS2 using the crystal structure of protozoan Babesia bovis DHFR‐TS (Begley et al ., ) as it shares ~43% sequence similarity (Figure b). The predicted structures suggest both DHFR‐TS1 and DHFR‐TS2 form canonical bifunctional DHFR‐TS enzymes whereby the DHFR domains (residues 21–198 and 64–242, respectively) form an eight‐stranded β‐sheet encased by four short α‐helical regions, linked to a C‐terminal TS domain (residues 223–519 and 271–565, respectively) by a long Class I type junctional region that has been shown to join adjacent DHFR monomers (O'Neil et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…To elucidate a structural basis for the difference in resistance profiles to DHFR inhibitors of the G137D and A71V mutants in DHFR‐TS1 and DHFR‐TS2, respectively, we modelled the structure of A. thaliana DHFR‐TS1 and DHFR‐TS2 using the crystal structure of protozoan Babesia bovis DHFR‐TS (Begley et al ., ) as it shares ~43% sequence similarity (Figure b). The predicted structures suggest both DHFR‐TS1 and DHFR‐TS2 form canonical bifunctional DHFR‐TS enzymes whereby the DHFR domains (residues 21–198 and 64–242, respectively) form an eight‐stranded β‐sheet encased by four short α‐helical regions, linked to a C‐terminal TS domain (residues 223–519 and 271–565, respectively) by a long Class I type junctional region that has been shown to join adjacent DHFR monomers (O'Neil et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…The high sequence and structural homology across TS enzymes from human and many parasite species, particularly within active site residues, creates a challenge for obtaining drug selectivity [42], [43]. The B. thailandensis TS protein (BTH_I1680, PDB: 3V8H) has an arginine residue substituted for a canonical active site tryptophan (W83 in E. coli ); arginine is also the side chain found in human TS (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of an effect of the C21 peptide on the fluorescence signal of T. gondii TS–DHFR in the presence of dUMP may explain why the inhibitory effect of the peptides was selective for the apo‐enzyme state. The crystal structure of the apo‐TS–DHFR from Babesia bovis , similar to the TS–DHFR from T. gondii in domain organization, showed that the apo form of the enzyme had increased disorder in both the TS and DHFR domains as compared to the dUMP‐bound structure . Peptides from human TS were also dependent on the apo‐enzyme state .…”
Section: Discussionmentioning
confidence: 56%
“…The crystal structure of the apo-TS-DHFR from Babesia bovis, similar to the TS-DHFR from T. gondii in domain organization, showed that the apo form of the enzyme had increased disorder in both the TS and DHFR domains as compared to the dUMP-bound structure. 9 Peptides from human TS were also dependent on the apo-enzyme state. 23 This further validates the role dUMP plays in transitioning the TS enzyme into a stable, active conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation